Integral representations for the double-diffusivity system on the half-line - Chatziafratis, Andreas; Aifantis, Elias C.; Carbery, Anthony; Fokas, Athanassios S. (Zeitschrift für Angewandte Mathematik und Physik, 2024)
A novel method is presented for explicitly solving inhomogeneous initial-boundary-value problems (IBVPs) on the half-line for a well-known coupled system of evolution partial differential equations. The so-called double-diffusion model, which is based on a simple, yet general, inhomogeneous diffusion configuration, describes accurately several important physical and mechanical processes and thus emerges in miscellaneous applications, ranging from materials science, heat-mass transport and solid–fluid dynamics, to petroleum and chemical engineering. For instance, it appears in nanotechnology and its inhomogeneous version has recently appeared in the area of lithium-ion rechargeable batteries. Our approach is based on the extension of the unified transform (also called the Fokas method), so that it can be applied to systems of coupled equations. First, we derive formally effective solution representations and then justify a posteriori their validity rigorously. This includes the reconstruction of the prescribed initial and boundary conditions, which requires careful analysis of the various integral terms appearing in the formulae, proving that they converge in a strictly defined sense. The novel solution formulae are also utilized to rigorously deduce the solution’s regularity properties near the boundaries of the spatiotemporal domain. In particular, we prove uniform convergence of the solution to the data, its rapid decay at infinity as well as its smoothness up to (and beyond) the boundary axes, provided certain data compatibility conditions at the quarter-plane corner are satisfied. As a sample of important applications of our analysis and investigation of the boundary behavior of the solution and its derivatives, we both prove a novel uniqueness theorem and construct a ‘non-uniqueness counterexample’. These supplement the preceding ‘constructive existence’ result, within the framework of well-posedness. Moreover, one of the advantages of the unified transform is that it yields representations which are defined on contours in the complex Fourier λ-plane, which exhibit exponential decay for large values of λ. This important characteristic of the solutions is expected to allow for an efficient numerical evaluation; this is envisaged in future numerical-analytic investigations. The new formulae and the findings reported herein are also expected to find utility in the study of questions pertaining to well-posedness for nonlinear counterparts too. In addition, our rigorous approach can be extended to IBVPs for other significant models of mathematical physics and potentially also to higher-dimensional and variable-coefficient cases.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 35A09; 35A22; 35A25; 35B65; 35C05; 35C15; 35G46; 35Q35; 35Q79; 44A15; 74F10; 74H05; 74H30; 74S70; 76F25; 76S05; Barenblatt’s pseudoparabolic equation; Cahn–Hilliard model; Closed-form solutions; Double-diffusion model; Fokas unified-transform method; Integral representations; Mechanics of solids; Nanotechnology; Nonhomogeneous initial-boundary-value problems on the quarter-plane; Rigorous analysis; Well-posedness